D/H Ratios on Saturn and Jupiter from Cassini CIRS - Pierel, J; Nixon, C; Lellouch, E; Fletcher, L; Bjoraker, G; Achterberg, R; Bezard, B; Hesman, B; Irwin, P; Flasar, F (IOP Publishing, 2017)
We present new measurements of the deuterium abundance on Jupiter and Saturn, showing evidence that Saturn's atmosphere contains less deuterium than Jupiter's. We analyzed far-infrared spectra from the Cassini Composite Infrared Spectrometer to measure the abundance of HD on both giant planets. Our estimate of the Jovian D/H = (2.95 ± 0.55) × 10−5 is in agreement with previous measurements by ISO/SWS: (2.25 ± 0.35) × 10−5, and the Galileo probe: (2.6 ± 0.7) × 10−5. In contrast, our estimate of the Saturn value of (2.10 ± 0.13) × 10−5 is somewhat lower than on Jupiter (by a factor of ), contrary to model predictions of a higher ratio: Saturn/Jupiter = 1.05–1.20. The Saturn D/H value is consistent with estimates for hydrogen in the protosolar nebula (2.1 ± 0.5) ×10−5, but its apparent divergence from the Jovian value suggests that our understanding of planetary formation and evolution is incomplete, which is in agreement with previous work.